FREQUENCY OF PERSISTANT BACKACHE IN PATIENTS OF SPINAL ANAESTHESIA IN THE ABSENCE OF PRIOR HISTORY OF BACKACHE: Persistant Backache in Patients of Spinal Anaesthesia - ., Maj Naveed Farhat; Rahman, Faiz ur; Janjua, Sarfraz Khan (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the frequency of persistant backache in patients of spinal anaesthesia in the absence of prior history of bachache. Study Design: Quasi experimental study. Place and Duration of Study: CMH Kharian from May 2008 to Sep 2009. Methods: Total 150 patients who were admitted at CMH Kharian during the study period were included in the study. The selection criteria included male and female patients above twenty years of age due for elective gynaecological, orthopaedics, urology and general surgical procedures. Only 112 patients reported for complete follow up for one year. Out of 112 patients, 61.6% were males while 38.4% were females. All patients with prior history of back pain were excluded from the study. Results: At the end of one year the frequency of persistent back pain after one year of spinal anaesthesia is (1/112) 0.89% in the absence of previous history of back pain. Conclusion: The results of this study indicate that frequency of persistant back pain after spinal anaesthesia in the absence of previous history of back pain is very low.